Feira, forma, dom. Assimetrias da sociação numa feira de Belém - CASTRO, Marina Ramos Neves de (Universidad de Buenos Aires, 2022)
The article describes sociability processes in a market in Belem, Para state’s capital, in the Brazilian Amazon, seeking to reflect on reciprocity and asymmetry processes present there. The article is the result of an eight-month ethnographic investigation. It’s ethnographic perspective leads to an interpretation and description of social interac tion as intersubjective dynamics. By observing the trading strategies and associations between merchants, customers and other individuals present at the market, we seek to understand reciprocity in its asymmetric aspects and the market itself as a social form. We aim to establish a dialogue with the reflections of Georg Simmel and Marcel Mauss, who in their analysis prioritize the relational dynamics of social reality. Looking into the relations of social subjects within the fair –traders, customers, public officials, among other stakeholders– we seek to glimpse the complexity of the inter-subjective process, reflecting on forms of reciprocity and gift in everyday life of the market.